A Recent Approach on Optic Disc Drusenoid Deposits with Hemifield Defects in a Patient with IgA Nephropathy - S. K. Prabhakar; P. V. Priyamvada (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
To describe emerging new OCT and Humphrey visual field findings is the objective of the study. Patients with IgA nephropathy (25-30%) develop end-stage renal disease within 20 years after diagnosis however information and evaluation concerning visual disturbances are insufficiently known, herein we present a known IgAN patient with associated visual haziness reporting to our ophthalmology department [1]. A previously treated 20-year old female patient for skin rashes, hematuria, and pain abdomen 8 months ago reported visual disruption in the right eye for the last one week. Features of leukocytoclastic vasculitis on skin biopsy and glomerular mesangial cell hyperplasia on renal biopsy inferred a clinical diagnosis of IgA nephropathy. Consequently, proteinuria manifested one month after administration of prednisolone 50 mg/day tapered for 8 months, Visual acuity of 6/9 in the right eye and 6/6 in the left eye with normal color vision recorded in addition to early signs of papilledema. Classically, on OCT, hyperreflective intense echoes were discovered in the optic disc, and accordingly inferior hemifield defects were established predominantly in the right eye on HFA. Total leucocyte count at11720 cells/cu mm and ESR 60 mm/hr by the Wintrobe method with the presence of albumin, RBCs, and pus cells on urine analysis in addition to positive occult stool blood detection. C3, C4, and ANCA panels revealed negative results and the USG abdomen disclosed fatty liver with mesenteric nodes. In conclusion, Optic disc drusenoid deposits corresponding with hemifield visual field defects detected in the current case study are possibly the associated early fundus manifestation of IgA nephropathy.